Human Resource Training: An Approach in Digital Era - Van Luan, Hoang (VNU Journal of Science: Policy and Management Studies, 2023)
There have been many publications on the role and requirements of human resources and human resource management in thedigital era. Many scholars and managers have suggested that human factors in general and human resources' level of digital competency in particular determine the speed and scope of digitalization. However, the thesis of ‘context makes the man’ suggested an approach to human resource training that can overcome the barrier of digital capacity constraints: Embedding human resources into the framework of digital application training to help develop digitally capable individuals. COVID-19 is considered as a big push in the application of digital technology in human activities, including human resource training and thereby, contributing to the improvement of human resources’ digital competence. This article focuses on a digital approach to human resource training that enhances the efficiency, adaptability, and convenience of human resources training while enabling training to quickly adapt to the rapid changes in science and technology. Keywords: Human Resource, Human Resource Training, Approach to Human Resource Training, Digital Era, Digital Technology.